Understanding Developers’ Work - A Visual Approach for Project Managers - Ferreira, Matheus Silva; Pereira Júnior, Paulo; Costa, Heitor Augustus Xavier (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
One of the Project Manager’s main activities is to lead the people involved in the project. This activity implies in assembling teams, recognizing the work done by developers, distributing knowledge in the project, among others. Understanding the developers’ work can support the Project Manager in leading the team. In this sense, different strategies have been proposed to provide information about the work done by developers. But, there are still gaps to be explored, such as considering the evolution of the software when visualizing how much the developers have worked and providing the visualization from different perspectives, including project information and individual developers’ work at multiple levels of granularity. In this paper, the Developer Tracker approach is presented to support the Project Manager in understanding the developers’ work. This approach has a set of steps, including SCV mining, calculating quantitative measures, and applying a software visualization technique. To evaluate Developer Tracker, a computational support used by 16 Project Managers from the software industry was developed in an experimental study. The results showed that, in general, the approach was useful in improving Project Managers’ understanding.